2013
DOI: 10.1063/1.4819449
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of the photocatalytic properties of TiO2 by (Fe+Mo) co-doping—A possible way to retard the recombination process

Abstract: Low visible light absorption and high charge carrier recombination rate are two main disadvantages of TiO2 as a photocatalyst which severely limit its practical applications. To overcome the problems, Fe mono-doped and (Fe+Mo) co-doped TiO2 were synthesized and studied. It was found that (Fe+Mo) co-doping can further increase the visible absorption and improve the photocatalytic property of TiO2 compared with Fe mono-doping; Fe mono-doping improves the photocatalytic property of TiO2 only at very low doping le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(27 citation statements)
references
References 25 publications
0
27
0
Order By: Relevance
“…Since most of the metal-oxide photocatalysts, including perovskites, have too large optical band gaps for visible light, many efforts have been directed to a reduction by chemical doping. For example, cation-cation codoping of TiO 2 has been investigated experimentally for (Ni/Zn/Mo, Fe) [1][2][3][4], (Co/Nb/Ta, Ni) [5][6][7], (Y, V) [8], (Sb, Cr) [9], (Rh, Sr) [10] and theoretically for (Ni, Fe) [11], (Rh, Nb) [12], (Mo/W, Mg/Ca) [13], (La, Mn) [14]. Other studies have addressed (La, Ag) codoping of CaTiO 3 [15], (Sn, Ga) codoping of BiFeO 3 [16], and (W, Fe/Mo) codoping of BiVO 4 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Since most of the metal-oxide photocatalysts, including perovskites, have too large optical band gaps for visible light, many efforts have been directed to a reduction by chemical doping. For example, cation-cation codoping of TiO 2 has been investigated experimentally for (Ni/Zn/Mo, Fe) [1][2][3][4], (Co/Nb/Ta, Ni) [5][6][7], (Y, V) [8], (Sb, Cr) [9], (Rh, Sr) [10] and theoretically for (Ni, Fe) [11], (Rh, Nb) [12], (Mo/W, Mg/Ca) [13], (La, Mn) [14]. Other studies have addressed (La, Ag) codoping of CaTiO 3 [15], (Sn, Ga) codoping of BiFeO 3 [16], and (W, Fe/Mo) codoping of BiVO 4 [17,18].…”
Section: Introductionmentioning
confidence: 99%
“…6b). It is concluded that high level doping may cause too many lattice defects, which can act as recombination centers for electron and holes so that they degrade the conversion performance [39]. The competitive growth of rutile when Mn content is higher than 6% may also influence the photo sensitivity of TiO 2 [40].…”
Section: Resultsmentioning
confidence: 99%
“…Since Fe 3+ in the 3d orbital is half lled, as Fe 3+ is doped into TiO 2 , the empty E g state is near the bottom of the conduction band, while the occupied t 2g state of Fe is located at the top of the valence band. 46 There are multiple electronic 2 T 1g ) or to the charge transfer transition between interacting iron ions via the conduction band (Fe 3+ + Fe 3+ / Fe 4+ + Fe 2+ ). 11,47,48 For rGO/Ag/ Fe-doped TiO 2 , there is a broad range absorption in the visible region, mainly due to the local surface plasmonic resonance (LSPR) effect of Ag nanoparticles.…”
Section: Optical Characterizationmentioning
confidence: 99%
“…53 As Fe was doped into TiO 2 , a new characteristic peak located at 575 cm À1 was attributed to the stretching vibration of the Fe-O bond. 46 Aer rGO connected with Fedoped TiO 2 -based specimens, several functional groups could be seen, such as the peak located at 1571 cm À1 corresponding to C]C aromatic bonding, and the lowering of the absorption peak at around 1705 cm À1 assigned to the C]O stretching accredited to rGO. Typically, Ti-O-Ti and Ti-O-C bonds can be seen at low frequency bands around 450 to 900 cm À1 , and their shiing towards a higher wavenumber, compared with Fedoped TiO 2 , indicates the chemical interaction of Fe-doped TiO 2 with rGO.…”
Section: Optical Characterizationmentioning
confidence: 99%